Fish Farming Methods In the Iraqi Marshes - Al-Mukhtar, Mustafa A. (Iraqi Journal of Aquaculture, 2022)
Fish farming methods that is suitable for the Iraqi marshes were classified in two main categories: water based methods and soil based methods. In the first category it was found that the floating net cages could be used in the rivers and the main branches, while the fixed net cages could be used in the shallowest water bodies. It was found that there is a good opportunity to use the Enclosures and Pens. The natural grazing method could be applied in the wide area all over the marsh, especially in the area which is enclosed by dams. In the second category the tidal ponds was found to be suitable in the lower parts of Al=Hammar marsh, While the dyke ponds could be used in high lands near the villages. It found that there was a good opportunity to use fish farming in the draining systems, and Fish-Cum-Rice system in the areas with agriculture activity. In addition the polyculture and Integrated fish farming cane be used as an environment-friendly techniques.